Anti-self-degradation high-purity ferrate water treatment agent and preparation method thereof
Patent Information
- Application Number
- CN202611373461.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-20
AI Technical Summary
其中,硅酸钠可在乙醇—水体系中通过调节pH发生缩聚,并在颗粒表面形成硅氧包覆层,但其形成的包覆层含有较多亲水性硅羟基,仍可能吸附和传递水分;石蜡、脂肪酸等疏水材料虽然能够提高阻湿性能,但致密疏水层又容易阻碍高铁酸钾投入水后的润湿和释放
[0026]与现有技术相比,本申请通过在高铁酸钾核心颗粒表面依次形成以甲基硅氧网络为连续相的内侧连续区和氧化镁富集的外侧区域,利用内侧甲基硅氧网络的致密疏水作用降低环境水分向高铁酸钾核心的渗透,抑制贮藏过程中的自衰减,同时利用外侧氧化镁在接触水体后形成的局部碱性微环境减缓Fe(VI)的水解分解,并对其释放过程进行调节;配合分阶段喷涂、二氧化碳中和缩聚及同步引入氧化镁的制备方式,可提高复合包覆层的连续性和层次稳定性,在保持较高有效高铁酸钾含量的同时,兼顾长期贮藏稳定性、有效Fe(VI)释放率及湿热贮藏后的水处理能力。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of water treatment agent technology, and in particular to a high-purity ferrate water treatment agent with anti-self-decay properties and its preparation method. Background Technology
[0002] Potassium ferrate possesses oxidation, disinfection, deodorization, and flocculation functions. Its reduction products are mainly ferric compounds, making it suitable for the removal of organic pollutants, nitrogenous pollutants, and microorganisms. However, potassium ferrate is sensitive to environmental moisture and is prone to self-decomposition due to moisture absorption during preparation, drying, and storage, leading to a decrease in the effective hexavalent iron content. Even with methods such as using high-purity raw materials and low-temperature crystallization to improve the purity of potassium ferrate, it is difficult to avoid the activity degradation caused by contact between the particle surface and moisture.
[0003] Existing technologies typically employ sodium silicate, silica, paraffin, fatty acids, or polymeric materials to coat potassium ferrate. Sodium silicate can undergo condensation polymerization in an ethanol-water system by adjusting the pH, forming a silica-oxygen coating layer on the particle surface. However, this coating layer contains numerous hydrophilic silanol groups, which may still adsorb and transfer moisture. While hydrophobic materials such as paraffin and fatty acids can improve moisture barrier properties, their dense hydrophobic layers can hinder the wetting and release of potassium ferrate upon immersion in water. These coating layers generally only provide passive barrier properties, failing to simultaneously ensure storage stability in humid environments and rapid release after water addition. Therefore, constructing a potassium ferrate coating structure that effectively blocks moisture during storage and allows for timely release upon immersion in water is a technical problem that needs to be solved in this field. Summary of the Invention
[0004] This invention provides a high-purity ferrate water treatment agent with anti-self-decay properties, comprising potassium ferrate core particles and a composite coating layer covering the surface of the potassium ferrate core particles;
[0005] The composite coating layer includes a continuous methylsiloxane network and magnesium oxide particles. The composite coating layer includes an inner continuous region near the potassium ferrate core particles and a magnesium oxide enrichment region near the outer surface of the composite coating layer along its thickness direction.
[0006] The inner continuous region uses the methylsiloxane network as the continuous phase, and the magnesium oxide particle content in the magnesium oxide enrichment region is higher than that in the inner continuous region.
[0007] It should be noted that during the storage stage, the methylsiloxane network in the inner continuous zone, relying on the continuous Si-O-Si framework and hydrophobic Si-CH3 groups, reduces the permeation rate of environmental moisture into the potassium ferrate core particles, thereby inhibiting the self-decomposition of ferrate ions. When the water treatment agent is added to the water, the water first enters the magnesium oxide enrichment zone, where magnesium oxide undergoes the hydration reaction MgO + H2O → Mg(OH)2. The generated Mg-OH active sites further react with the residual Si-OH or Si-O groups in the methylsiloxane network. - Site reactions form Si-O-Mg bonds and / or magnesium-silicon-oxygen hydration structures. These reactions alter the local composition, cross-linking mode, and hydrophilicity / hydrophobicity of the methylsiloxane network within the magnesium oxide-rich region. Simultaneously, the volume increase resulting from magnesium oxide hydration creates localized stress within the coating layer, prompting the formation of microcracks and moisture transport channels in the outer network, thus gradually releasing potassium ferrate. The magnesium hydroxide generated during hydration also creates a localized alkaline environment, slowing the ineffective decomposition of released ferrate ions. Therefore, during dry storage, the inner continuous region of this composite coating layer provides moisture barrier protection. Upon immersion in water, the coating layer undergoes responsive reconstruction through magnesium oxide hydration and its interfacial reaction with the methylsiloxane network, thereby balancing the storage stability and water release performance of potassium ferrate.
[0008] As a preferred technical solution for a high-purity ferrate water treatment agent with anti-self-decay, based on 100 parts by mass of the potassium ferrate core particles, the effective substance of potassium methylsilicate used to form the methylsiloxane network is 1 to 3 parts by mass, and the magnesium oxide particles are 0.2 to 0.8 parts by mass.
[0009] It should be noted that controlling the amount of potassium methylsilicate and magnesium oxide particles to 1-3 parts by mass and 0.2-0.8 parts by mass, respectively, can ensure that the magnesium oxide enrichment zone has a suitable hydration response while forming a continuous moisture-barrier methylsiloxane network. This avoids insufficient moisture barrier due to too low coating amount or hindered potassium ferrate release due to too high coating amount.
[0010] As a preferred technical solution for a high-purity ferrate water treatment agent with anti-self-decay properties, the magnesium oxide particles are highly active light-calcined magnesium oxide particles, and the median particle size D of the magnesium oxide particles is... 50 The value is 0.2–2 μm.
[0011] It should be noted that the median particle size D is used. 50 The high-activity lightly calcined magnesium oxide with a particle size of 0.2–2 μm is conducive to the uniform distribution of magnesium oxide on the outer side of the composite coating layer, and to rapid hydration and interfacial interaction after entering water, avoiding slow response due to excessively large particle size or particle agglomeration due to excessively small particle size.
[0012] In addition, this application also provides a method for preparing a high-purity ferrate water treatment agent with anti-self-decay properties, characterized by comprising the following steps:
[0013] S1. Vacuum dry the potassium ferrate core particles and cool them in dry nitrogen gas;
[0014] S2. Place the potassium ferrate core particles in a dry nitrogen flow bed, spray 70% to 90% of the total amount of potassium methylsilicate coating liquid onto the surface of the potassium ferrate core particles, and simultaneously introduce nitrogen gas containing carbon dioxide into the spraying area to neutralize and condense potassium methylsilicate on the surface of the potassium ferrate core particles to form an inner continuous zone.
[0015] S3. While continuing to spray the remaining potassium methylsilicate coating solution, dry magnesium oxide powder is simultaneously fed into the same spraying area, so that the magnesium oxide powder is concentrated in the outer area of the composite coating layer, forming a magnesium oxide enrichment area.
[0016] S4. The obtained particles are dried and shaped using dry nitrogen gas, followed by low-temperature vacuum drying to obtain the anti-self-decaying high-purity ferrate water treatment agent.
[0017] It should be noted that in step S1, free and adsorbed water on the surface of the potassium ferrate core particles are removed by vacuum drying, and the particles are cooled in dry nitrogen to prevent re-hygroscopication and self-decomposition during cooling. In step S2, 70%–90% of the total amount of potassium methylsilicate coating solution is sprayed in, and carbon dioxide is used to neutralize and condense the potassium methylsilicate, so that it preferentially forms a continuous methylsiloxane inner moisture-barrier zone under conditions unaffected by magnesium oxide particles. In step S3, the remaining potassium methylsilicate coating solution forms a moist interface, and while continuing to spray the solution, the solution is simultaneously... In step S4, dry magnesium oxide powder is fed in, causing the magnesium oxide to adhere and be fixed to the outside of the coating layer, thereby forming an enriched structure with the magnesium oxide content increasing from the inside to the outside. In step S5, volatile components in the coating layer are removed and initially shaped by drying nitrogen gas. Then, low-temperature vacuum drying is used to further remove residual moisture and solvents, which fixes the composite coating layer structure while avoiding the thermal decomposition of potassium ferrate. This allows the inner continuous zone to play a moisture-proof protection role during storage, while the outer magnesium oxide enriched zone achieves responsive reconstruction after being introduced into water through hydration and interfacial interaction with the methylsiloxane network.
[0018] In a preferred technical solution for the preparation method of a high-purity ferrate water treatment agent with anti-self-decay, in step S1, the vacuum drying temperature is 30-40℃ and the time is 2-4h, and the moisture content of the dried potassium ferrate core particles is not higher than 0.2%; the dew point of the drying nitrogen gas used to cool the potassium ferrate core particles is not higher than -40℃.
[0019] It should be noted that vacuum drying at 30-40℃ for 2-4 hours and controlling the moisture content of the core particles to below 0.2% can effectively remove surface moisture while avoiding the thermal decomposition of potassium ferrate. Nitrogen gas with a dew point not higher than -40℃ can prevent the particles from reabsorbing moisture during the cooling process.
[0020] A preferred technical solution for the preparation method of a high-purity ferrate water treatment agent with anti-self-decay properties is provided, wherein the potassium methylsilicate coating solution is composed of potassium methylsilicate, ethanol and water, wherein the volume ratio of ethanol to water is 80:20 to 90:10, and the effective concentration of potassium methylsilicate in the potassium methylsilicate coating solution is 2% to 5%.
[0021] It should be noted that controlling the volume ratio of ethanol to water to 80:20 to 90:10 and the effective concentration of potassium methylsilicate to 2% to 5% can balance the solubility stability of potassium methylsilicate, the atomization performance of the coating solution and the continuity of film formation, while reducing the direct effect of water on the potassium ferrate core particles.
[0022] In a preferred embodiment of a method for preparing a high-purity ferrate water treatment agent with anti-self-decay properties, in steps S2 and S3, the temperature of the potassium ferrate core particles is 15–25°C, the volume content of carbon dioxide in the nitrogen gas introduced into the spraying area is 0.2%–1.0%, and the median particle size D of the droplets formed after atomization of the potassium methylsilicate coating liquid is... 50 The size ranges from 5 to 30 μm.
[0023] It should be noted that the core particle temperature is controlled at 15–25℃, the carbon dioxide volume content is controlled at 0.2%–1.0%, and the atomized droplet D… 50 By controlling the size to 5–30 μm, potassium methylsilicate can be neutralized and condensed at an appropriate rate and uniformly deposited on the particle surface while suppressing the thermal decomposition of potassium ferrate and local overwetting.
[0024] In a preferred technical solution for the preparation method of a high-purity ferrate water treatment agent with anti-self-decay, in step S4, after stopping the spraying, dry nitrogen gas is continuously introduced for 10-20 minutes, followed by vacuum drying at 30-40℃ and a gauge pressure of -0.095 to -0.08MPa for 2-6 hours.
[0025] It should be noted that after stopping the spraying, continue to introduce dry nitrogen gas for 10 to 20 minutes, and then vacuum dry at 30 to 40°C and a gauge pressure of -0.095 to -0.08 MPa for 2 to 6 hours. This can gradually remove ethanol, water and other volatile components from the coating layer, and fix the methylsiloxane network and magnesium oxide enrichment structure while avoiding the thermal damage of potassium ferrate.
[0026] Compared with existing technologies, this application sequentially forms an inner continuous region with a methylsiloxane network as the continuous phase and an outer region enriched with magnesium oxide on the surface of potassium ferrate core particles. The dense hydrophobic effect of the inner methylsiloxane network reduces the penetration of environmental moisture into the potassium ferrate core and inhibits self-attenuation during storage. At the same time, the local alkaline microenvironment formed by the outer magnesium oxide after contact with water slows down the hydrolysis and decomposition of Fe(VI) and regulates its release process. Combined with the preparation method of staged spraying, carbon dioxide neutralization condensation and simultaneous introduction of magnesium oxide, the continuity and layer stability of the composite coating layer can be improved. While maintaining a high effective potassium ferrate content, it also takes into account long-term storage stability, effective Fe(VI) release rate and water treatment capacity after humid heat storage. Attached Figure Description
[0027] Figure 1 The Fourier transform infrared spectra of the potassium ferrate core particles, the methylsiloxane inner intermediate product, and the final composite coated product before and after hydrolysis during the preparation process of Example 1 are shown.
[0028] Figure 2 The cumulative release rate of Fe(VI) over time is shown in the graphs of the products obtained in Examples 1 to 4 and Comparative Examples 1 to 3.
[0029] Figure 3 Line graphs showing the change in effective K2FeO4 content with storage time during room temperature storage of the products obtained in Examples 1 to 4 and Comparative Examples 1 to 3. Detailed Implementation
[0030] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0031] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0032] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0033] Example 1
[0034] This embodiment provides a high-purity ferrate water treatment agent with anti-self-decay properties, the preparation method of which includes the following steps:
[0035] S1. Weigh out particles with a purity of 95% and a median particle size D. 50 100g of potassium ferrate core particles with a diameter of 50μm were placed in a vacuum drying oven and vacuum dried for 2 hours at 30℃ and a gauge pressure of -0.08MPa. The Karl Fischer method was used to confirm that the moisture content of the dried particles was no higher than 0.2%. After drying, dry nitrogen gas with a dew point of -40℃ was introduced into the vacuum drying oven to cool the potassium ferrate core particles to 15℃ under the protection of dry nitrogen gas.
[0036] S2. Weigh 2.50g of potassium methylsilicate stock solution with an effective substance content of 40wt%, including 1.00g of potassium methylsilicate effective substance; mix the potassium methylsilicate stock solution with 10.30g of deionized water, stir at 300r / min for 5min, then slowly add 47.2mL of anhydrous ethanol, and continue stirring for 10min to obtain a potassium methylsilicate coating solution with a total mass of approximately 50g; the effective substance mass concentration of potassium methylsilicate in the coating solution is 2%, and the volume ratio of ethanol to water is 80:20. Add the potassium ferrate core particles obtained in step S1 to a dry nitrogen fluidized bed, control the dew point of the fluidizing nitrogen to -40℃ and the apparent gas velocity to 0.7m / s, and maintain the particle temperature at 15℃; add carbon dioxide to the fluidizing nitrogen to make the carbon dioxide volume content 0.2%, and atomize the coating solution to a median particle size D. 50 35g of coating liquid is sprayed into 5μm droplets at a rate of 0.8g / min, which is 70% of the total amount of coating liquid used, so that potassium methylsilicate is neutralized and condensed on the surface of the core particles to form an inner continuous region.
[0037] S3. Maintaining constant particle temperature, fluidization state, and carbon dioxide volume content, continue spraying the remaining 15g of potassium methylsilicate coating solution at a rate of 0.8g / min; simultaneously, uniformly feed 0.20g of highly active lightly calcined magnesium oxide powder, which has been vacuum dried at 105℃ for 2h and cooled in dry nitrogen, into the same spraying area. The median particle size D of the magnesium oxide powder is... 50 The thickness is 0.2 μm, and the average feeding speed of the magnesium oxide powder is controlled to be about 0.011 g / min, so that the magnesium oxide powder is concentrated and fixed on the outer area of the composite coating layer.
[0038] S4. After stopping the spraying and magnesium oxide powder feeding, continue to purge with dry nitrogen gas at a dew point of -40℃ for 10 minutes to dry and shape the obtained particles; then transfer the particles to a vacuum drying oven and vacuum dry them for 2 hours at 30℃ and a gauge pressure of -0.08MPa. Cool them to room temperature under the protection of dry nitrogen gas and seal them for storage to obtain a high-purity ferrate water treatment agent with anti-self-decay.
[0039] Example 2
[0040] This embodiment provides a high-purity ferrate water treatment agent with anti-self-decay properties, the preparation method of which includes the following steps:
[0041] S1. Weigh out particles with a purity of 96% and a median particle size D. 50 100g of potassium ferrate core particles with a diameter of 80μm were vacuum dried for 2.5h at 33℃ and a gauge pressure of -0.085MPa to confirm that the moisture content of the dried particles was not higher than 0.2%. Then, dry nitrogen gas with a dew point of -45℃ was introduced to cool the potassium ferrate core particles to 18℃.
[0042] S2. Weigh 4.50g of potassium methylsilicate stock solution with an effective substance content of 40wt%, including 1.80g of potassium methylsilicate effective substance; mix the stock solution with 9.30g of deionized water evenly, and then slowly add 58.6mL of anhydrous ethanol to obtain a potassium methylsilicate coating solution with a total mass of approximately 60g; the effective substance mass concentration of potassium methylsilicate in the coating solution is 3%, and the volume ratio of ethanol to water is 83:17. Place the dried core particles in a dry nitrogen fluidized bed, control the dew point of the fluidized nitrogen to be -45℃, the apparent gas velocity to be 0.7m / s, the particle temperature to be 18℃, and the volume content of carbon dioxide in the fluidized nitrogen to be 0.4%; atomize the coating solution to a median particle size D. 50 45g of coating liquid is sprayed into 12μm droplets at a rate of 0.8g / min, and the sprayed amount is 75% of the total amount of coating liquid used, forming an inner continuous zone.
[0043] S3. Maintaining the gas composition and particle temperature within the fluidized bed, continue spraying the remaining 15g of coating liquid at a rate of 0.8g / min, while simultaneously uniformly feeding 0.40g of median particle size D into the same spraying area. 50 The magnesium oxide powder is dry, highly active, lightly calcined, and has a particle size of 0.8 μm. The average feeding rate of the magnesium oxide powder is controlled to be approximately 0.021 g / min, so that the magnesium oxide particles are concentrated on the outer side of the composite coating layer.
[0044] S4. After spraying, continue to purify with dry nitrogen gas at a dew point of -45℃ for 13 minutes, then vacuum dry at 33℃ and a gauge pressure of -0.085MPa for 3 hours. Cool and seal under dry nitrogen protection to obtain a high-purity ferrate water treatment agent with anti-self-decay properties.
[0045] Example 3
[0046] This embodiment provides a high-purity ferrate water treatment agent with anti-self-decay properties, the preparation method of which includes the following steps:
[0047] S1. Weigh out particles with a purity of 97% and a median particle size D. 50100g of potassium ferrate core particles with a diameter of 120μm were vacuum dried for 3.5h at 37℃ and a gauge pressure of -0.09MPa to confirm that the moisture content of the dried particles was not higher than 0.2%. Then, dry nitrogen gas with a dew point of -50℃ was introduced to cool the potassium ferrate core particles to 22℃.
[0048] S2. Weigh 6.00g of potassium methylsilicate stock solution with an effective substance content of 40wt%, including 2.40g of potassium methylsilicate effective substance; mix the stock solution with 5.56g of deionized water evenly, and then slowly add 61.4mL of anhydrous ethanol to obtain a potassium methylsilicate coating solution with a total mass of approximately 60g; the effective substance mass concentration of potassium methylsilicate in the coating solution is 4%, and the volume ratio of ethanol to water is 87:13. Place the dried core particles in a dry nitrogen fluidized bed, control the dew point of the fluidizing nitrogen to be -50℃, the apparent gas velocity to be 0.7m / s, the particle temperature to be 22℃, and the volume content of carbon dioxide in the fluidizing nitrogen to be 0.7%; atomize the coating solution to a median particle size D. 50 51g of coating liquid was sprayed into the solution at a rate of 0.8g / min, with the sprayed amount being 85% of the total amount of coating liquid used, to form an inner continuous zone.
[0049] S3. Maintaining the gas composition and particle temperature within the fluidized bed, continue spraying the remaining 9g of coating liquid at a rate of 0.6g / min, while simultaneously uniformly feeding 0.60g of median particle size D into the same spraying area. 50 The magnesium oxide powder is dry, highly active, lightly calcined, and has a particle size of 1.4 μm. The average feeding rate of the magnesium oxide powder is controlled at 0.040 g / min, so that the magnesium oxide particles are concentrated and fixed on the outside of the composite coating layer.
[0050] S4. After spraying, continue to purify with dry nitrogen gas at a dew point of -50℃ for 17 minutes, then vacuum dry at 37℃ and a gauge pressure of -0.09MPa for 4.5 hours. Cool and seal under dry nitrogen protection to obtain a high-purity ferrate water treatment agent with anti-self-decay properties.
[0051] Example 4
[0052] This embodiment provides a high-purity ferrate water treatment agent with anti-self-decay properties, the preparation method of which includes the following steps:
[0053] S1. Weigh out particles with a purity of 98% and a median particle size D. 50 100g of potassium ferrate core particles with a diameter of 150μm were vacuum dried for 4h at 40℃ and a gauge pressure of -0.095MPa to confirm that the moisture content of the dried particles was not higher than 0.2%. Then, dry nitrogen gas with a dew point of -55℃ was introduced to cool the potassium ferrate core particles to 25℃.
[0054] S2. Weigh 7.50g of potassium methylsilicate stock solution with an effective substance content of 40wt%, including 3.00g of potassium methylsilicate effective substance; mix the stock solution with 2.54g of deionized water evenly, and then slowly add 63.3mL of anhydrous ethanol to obtain a potassium methylsilicate coating solution with a total mass of approximately 60g; the effective substance mass concentration of potassium methylsilicate in the coating solution is 5%, and the volume ratio of ethanol to water is 90:10. Place the dried core particles in a dry nitrogen fluidized bed, control the dew point of the fluidizing nitrogen to be -55℃, the apparent gas velocity to be 0.7m / s, the particle temperature to be 25℃, and the volume content of carbon dioxide in the fluidizing nitrogen to be 1.0%; atomize the coating solution to a median particle size D. 50 54g of coating liquid, consisting of 30μm droplets, is sprayed at a rate of 0.8g / min, representing 90% of the total amount of coating liquid used, to form an inner continuous zone.
[0055] S3. Maintaining the gas composition and particle temperature within the fluidized bed, continue spraying the remaining 6g of coating liquid at a rate of 0.4g / min, while simultaneously uniformly feeding 0.80g of median particle size D into the same spraying area. 50 The magnesium oxide powder is dry, highly active, and lightly calcined, with a particle size of 2 μm. The average feeding rate of the magnesium oxide powder is controlled to be approximately 0.053 g / min, so that the magnesium oxide particles are concentrated on the outer side of the composite coating layer.
[0056] S4. After spraying, continue to purify with dry nitrogen gas at a dew point of -55℃ for 20 minutes, then vacuum dry at 40℃ and a gauge pressure of -0.095MPa for 6 hours. Cool and seal under dry nitrogen protection to obtain a high-purity ferrate water treatment agent with anti-self-decay properties.
[0057] Compare with Example 1
[0058] The difference between this comparative example and Example 1 is that potassium methylsilicate is not added. The potassium methylsilicate in the coating solution used in Example 1 is removed and replenished with an equal volume of a mixed solvent with the same ethanol / water ratio. In step S2, the mixed solvent without potassium methylsilicate is sprayed in according to the same spray volume, spray speed, and fluidization conditions as in Example 1. In step S3, the same amount of magnesium oxide as in Example 1 is dispersed in the remaining mixed solvent and sprayed onto the surface of the potassium ferrate core particles. Subsequent treatment is the same as in Example 1, yielding control sample C1.
[0059] Compare with Example 2
[0060] The difference between this comparative example and Example 1 is that magnesium oxide is not added. Steps S1 and S2 are the same as in Example 1; in step S3, only the remaining potassium methylsilicate coating solution is sprayed in, and magnesium oxide is not added simultaneously. The subsequent treatment is the same as in Example 1, resulting in control sample C2.
[0061] Compare with Example 3
[0062] The total amounts of potassium ferrate, potassium methylsilicate, and magnesium oxide used in this comparative example are the same as in Example 1, except that the staged coating is omitted. All the potassium methylsilicate coating solution is mixed with all the magnesium oxide to form a spray dispersion, which is sprayed in one go while the potassium ferrate core particles are in a fluidized state. During the spraying process, carbon dioxide is introduced in the same total amount as in Example 1. After spraying, drying and post-treatment are performed under the same conditions as in Example 1 to obtain control sample C3.
[0063] Performance testing methods
[0064] 1. Test of effective potassium ferrate content: Accurately weigh 0.1000 g of the sample to be tested, add 1 mol / L potassium hydroxide solution pre-cooled to 5-10℃ and make up to 100 mL, shake for 1 min to fully dissolve the potassium ferrate, then centrifuge at 5000 r / min for 3 min, take the supernatant for UV-Vis spectrophotometry; use 1 mol / L potassium hydroxide solution as blank, measure the absorbance at 505 nm, and calculate the Fe(VI) concentration in the solution according to the calibrated potassium ferrate standard curve, and further calculate the mass percentage of effective potassium ferrate in the sample.
[0065] 2. Self-attenuation performance test during room temperature storage: 10.0 g of each group of samples were weighed and placed into brown glass bottles of the same specifications. The bottles were sealed under a dry nitrogen atmosphere and stored at 25±2℃ in the dark. Samples were taken at 0, 7, 14, 30, 60, and 90 days of storage. The effective content at each time point was determined according to the above-mentioned method for testing effective potassium ferrate content. The effective content before storage was defined as C0, and the effective content after storage for t days was defined as C... t Press C t Calculate the retention rate of active ingredients by C0×100%, and then calculate it according to (C0-C0). t ) / C0×100% calculates the self-attenuation rate.
[0066] 3. Fe(VI) release performance test in water: Weigh equal masses of samples from each group to ensure equivalent initial effective potassium ferrate content. Add the samples to 1000 mL of 10 mmol / L borate buffer solution at 25±1℃ and pH 9.0, and stir at 200 r / min. Take 2 mL of the mixture at 0.5 min, 1 min, 2 min, 5 min, 10 min, 20 min, 30 min, and 60 min, and immediately add 18 mL of 1 mol / L potassium hydroxide solution to stabilize Fe(VI). After centrifugation to remove suspended particles, measure the absorbance at 505 nm and calculate the Fe(VI) concentration according to the standard curve. After sampling, add an equal volume of buffer solution and perform volume correction. Plot the Fe(VI) cumulative release rate-time curve accordingly.
[0067] 4. Water treatment performance test after storage: The samples from Example 1 and each control example were first stored at 40℃ and 75% relative humidity for 14 days. Then, the same product dosage was added to simulated methylene blue wastewater with an initial concentration of 20 mg / L. The product dosage was 100 mg / L. The initial pH of the system was adjusted to 7.0, and the mixture was stirred at 200 r / min for 30 min at 25±1℃. Afterward, it was allowed to stand for 30 min and filtered through a 0.45 μm filter membrane. The absorbance of the filtrate was measured at 664 nm. Simulated wastewater without product was used as a blank control. The treatment performance was determined according to (A0-A...). t ) / A0×100% to calculate the decolorization rate.
[0068] Table 1 Initial effective potassium ferrate content and water treatment performance after humid heat storage
[0069]
[0070] Combined with Example 1 and Figure 1 It can be seen that the potassium ferrate core particles obtained from S1 are at 808 cm⁻¹ -1 and 324 cm -1 The spectrum shows characteristic absorption peaks of ferrate in the vicinity; after step S2, a new peak at 2960 cm⁻¹ appears in the spectrum. -1 1260 cm -1 1120~1030 cm -1 840 cm -1 and 460 cm -1 The nearby absorption peaks indicate that a continuous coating layer containing methylsiloxane structures has formed on the surface of the core particles; the final composite coated product obtained in step S4 further shows a 520 cm⁻¹ absorption peak before hydrolysis. -1 The nearby Mg-O absorption peak indicates that magnesium oxide particles have been introduced to the outside of the coating layer. After hydrolysis, at 3695 cm⁻¹... -1 3420 cm-1 1635 cm -1 and 580cm -1 Absorption is enhanced in the vicinity, while at 1090–950 cm⁻¹ -1 The widening and changes in the region indicate that magnesium oxide underwent hydration accompanied by structural reconstruction of the silicon-oxygen interface, while the 2960 cm² area... -1 and 1260 cm -1 The nearby methylsiloxane characteristic peak and 808 cm⁻¹ -1 The characteristic peaks of ferrate ions in the vicinity are still preserved, indicating that the continuous methylsiloxane region on the inner side was not rapidly destroyed during the hydrolysis process. It can work in conjunction with the water absorption, hydration and alkaline buffering effect of the magnesium oxide enrichment region on the outer side to slow down the diffusion of water to the potassium ferrate core and the decomposition of ferrate ions, thereby improving the product's resistance to hydrolysis and self-decay.
[0071] Combined with Examples 1 to 4, Table 1, Figure 2 as well as Figure 3 It can be shown that the initial effective K2FeO4 content of the products obtained in Examples 1 to 4 is 92.71% to 94.28%, and they all exhibit a relatively slow Fe(VI) release process in water, with a final effective cumulative release rate of 95.2% to 97.0%. Furthermore, the effective component retention rate remains at 94.6% to 97.0% after 90 days of storage at room temperature. After 14 days of storage at 40°C and 75% relative humidity, the methylene blue decolorization rate still reaches 88.8% to 94.1%. Among these, Example 3 exhibits a relatively slow release rate but a high storage retention rate, while Example 4 combines a high effective release rate and a high decolorization rate. This demonstrates that within the range of potassium methylsilicate, magnesium oxide dosage, and magnesium oxide particle size specified in this application, a composite coating layer with moisture-proof barrier and water contact stability can be formed. The storage stability, release rate, and water treatment performance can be adjusted by regulating the dosage of the coating components.
[0072] Combined with Example 1, Comparative Example 1, and Table 1, Figure 2 as well as Figure 3 It can be seen that, due to the absence of a continuous methylsiloxane inner layer in Comparative Example 1, the amount of non-reactive coating material used was relatively small, resulting in an initial effective K2FeO4 mass fraction of 95.12%, slightly higher than 94.28% in Example 1. However, this difference mainly stems from the mass dilution effect of the coating material and does not necessarily indicate better stability. Comparative Example 1 exhibited a significant burst release at the initial stage of water contact, with the final effective cumulative release rate decreasing to approximately 90.0%. After 90 days of storage at room temperature, the retention rate of the effective component was only 63.8%, and the methylene blue decolorization rate after humid heat storage was only 46.5%, significantly lower than 96.1% and 93.0% in Example 1, respectively. This indicates that the continuous methylsiloxane inner layer can reduce the migration of environmental moisture to the potassium ferrate core, inhibit self-attenuation during storage, and prevent the product from releasing too quickly after entering water.
[0073] Combined with Example 1, Comparative Example 2, and Table 1, Figure 2 as well as Figure 3 It can be seen that the initial effective K2FeO4 content of Example 1 and Control Example 2 were 94.28% and 94.46%, respectively, which were basically equivalent. However, the final effective Fe(VI) cumulative release plateau of Control Example 2, which did not have a magnesium oxide enrichment outer layer, was only about 85.0%, the effective component retention rate after 90 days of storage at room temperature was 78.4%, and the methylene blue decolorization rate after humid heat storage was 64.2%, both significantly lower than that of Example 1. This indicates that the outer magnesium oxide enrichment zone can not only further reduce the impact of surface moisture on potassium ferrate, but also form a local alkaline microenvironment after the product comes into contact with water, slowing down the hydrolysis and decomposition of released Fe(VI), improving the release and recovery rate of effective Fe(VI), and enhancing the water treatment performance after storage.
[0074] Combined with Example 1, Comparative Example 3, and Table 1, Figure 2 as well as Figure 3 It can be seen that Control Example 3, which used a one-step mixed coating, failed to form an inner continuous methylsiloxane region and an outer magnesium oxide enrichment region. Its initial effective K2FeO4 content was only 90.38%, and the water release process showed a significant rapid release in the early stage, with a final effective cumulative release rate of approximately 88.0%. After 90 days of storage at room temperature, the effective component retention rate was only 69.2%, and the methylene blue decolorization rate after humid heat storage was only 54.8%, all significantly lower than that of Example 1. This indicates that pre-condensing most of the potassium methylsilicate coating solution to form a continuous inner layer, and then simultaneously introducing the remaining coating solution and magnesium oxide to form an outer enrichment region, is a necessary condition for obtaining a complete hierarchical composite coating structure. Simply mixing the components in one step is insufficient to simultaneously achieve moisture barrier, alkaline stability, and effective release regulation.
[0075] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A high-purity ferrate water treatment agent with anti-self-decay properties, characterized in that, It includes potassium ferrate core particles and a composite coating layer covering the surface of the potassium ferrate core particles; The composite coating layer includes a continuous methylsiloxane network and magnesium oxide particles. The composite coating layer includes an inner continuous region near the potassium ferrate core particles and a magnesium oxide enrichment region near the outer surface of the composite coating layer along its thickness direction. The inner continuous region uses the methylsiloxane network as the continuous phase, and the magnesium oxide particle content in the magnesium oxide enrichment region is higher than that in the inner continuous region.
2. The anti-self-decaying high-purity ferrate water treatment agent according to claim 1, characterized in that, Based on 100 parts by mass of the potassium ferrate core particles, the effective material of potassium methylsilicate used to form the methylsiloxane network is 1 to 3 parts by mass, and the magnesium oxide particles are 0.2 to 0.8 parts by mass.
3. The anti-self-decaying high-purity ferrate water treatment agent according to claim 1, characterized in that, The magnesium oxide particles are highly active lightly calcined magnesium oxide particles, and the median particle size D of the magnesium oxide particles is... 50 The value is 0.2–2 μm.
4. A method for preparing a high-purity ferrate water treatment agent with anti-self-decay properties, used to prepare the high-purity ferrate water treatment agent with anti-self-decay properties according to any one of claims 1 to 3, characterized in that, Includes the following steps: S1. Vacuum dry the potassium ferrate core particles and cool them in dry nitrogen gas; S2. Place the potassium ferrate core particles in a dry nitrogen flow bed, spray 70% to 90% of the total amount of potassium methylsilicate coating liquid onto the surface of the potassium ferrate core particles, and simultaneously introduce nitrogen gas containing carbon dioxide into the spraying area to neutralize and condense potassium methylsilicate on the surface of the potassium ferrate core particles to form an inner continuous zone. S3. While continuing to spray the remaining potassium methylsilicate coating solution, dry magnesium oxide powder is simultaneously fed into the same spraying area, so that the magnesium oxide powder is concentrated in the outer area of the composite coating layer, forming a magnesium oxide enrichment area. S4. The obtained particles are dried and shaped using dry nitrogen gas, followed by low-temperature vacuum drying to obtain the anti-self-decaying high-purity ferrate water treatment agent.
5. The preparation method according to claim 4, characterized in that, In step S1, the vacuum drying temperature is 30-40℃ and the time is 2-4 hours. The moisture content of the dried potassium ferrate core particles is not higher than 0.2%. The dew point of the drying nitrogen gas used to cool the potassium ferrate core particles is not higher than -40℃.
6. The preparation method according to claim 4, characterized in that, The potassium methylsilicate coating solution is composed of potassium methylsilicate, ethanol and water, wherein the volume ratio of ethanol to water is 80:20 to 90:10, and the effective concentration of potassium methylsilicate in the potassium methylsilicate coating solution is 2% to 5%.
7. The preparation method according to claim 4, characterized in that, In steps S2 and S3, the temperature of the potassium ferrate core particles is 15–25°C, the volume content of carbon dioxide in the nitrogen gas introduced into the spraying area is 0.2%–1.0%, and the median particle size D of the droplets formed after atomization of the potassium methylsilicate coating liquid is... 50 The size is 5–30 μm.
8. The preparation method according to claim 4, characterized in that, In step S4, after stopping the spraying, continue to introduce dry nitrogen gas for 10-20 minutes, and then vacuum dry for 2-6 hours at 30-40℃ and gauge pressure of -0.095 to -0.08MPa.